CHECKLIST OF VESPID SPECIES (INSECTA: HYMENOPTERA: VESPIDAE) OCCURRING IN INDONESIAN ARCHIPELAGO - Hari Nugroho; Jun-ichi Kojima; James M Carpenter (Treubia, 2011)
A total of 383 vespid species belonging to 63 genera from Indonesia are listed, together with information of the type material deposited in the Museum Zoologicum Bogoriense (MZB). The references of their distribution in Indonesia are also provided.